A ROLE OF FAMILY IS IN WARNING OF OFFENCES MINOR (CRIMINAL LAW AND CRIMINOLOGY DESCRIPTION) - Raisa Anuarovna Орсаева (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
The article of problem minor and the influence of family in notice. Also the question of notice criminality среди minors. Also consider the question about warning of criminality minor.